Non-adherence to anti-TB drugs among TB/HIV co-infected patients in Mbarara Hospital Uganda: Prevalence and associated factors - Amuha, Monica G (Makerere Medical School, 2009)
BACKGROUND: Non-adherence to treatment remains a major obstacle to efficient tuberculosis control in developing countries. The dual infection of Tuberculosis and HIV presents further adherence problems because of high pill burden and adverse effects. This poses a risk of increased multi-drug resistant TB. However, the prevalence of non-adherence and its associated factors have not been studied in these patients in Uganda. OBJECTIVES: To determine the prevalence and factors associated with non-adherence to anti-TB drugs among TB/HIV co-infected patients in Mbarara hospital. METHODS: A cross-sectional study with qualitative and quantitative data collection methods was conducted among TB/HIV co-infected adults in Mbarara hospital from January to March 2008. Consecutive sampling was used to select 140 participants. Adherence was assessed over a 5-day period prior to the interview using patients self-reports. Data was collected using an interviewer administered questionnaire. Qualitative data was collected through key informant interviews using a topic guide and was analyzed manually. Quantitative data was analyzed using STATA version 8. Logistic regression was used to determine factors associated with nonadherence. RESULTS: The prevalence of non-adherence was 25% (95% CI=17.8–32%). Being on continuous phase of the TB regimen was significantly associated with non-adherence (OR=6.24, p<0.001). Alcohol consumption, being on antiretroviral therapy and smoking confounded the relationship between stage of the TB regimen and non-adherence. CONCLUSION: The prevalence of non-adherence was high. Patients that are on continuous phase of TB treatment should be supported to continue taking their drugs. In addition, patients that drink alcohol; smoke and those not on ART should be targeted with interventions to improve adherence.